USM TO COLLABORATE WITH THE UNIVERSITY OF JOS NIGERIA - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 14 June 2016 – Universiti Sains Malaysia (USM) is taking another significant step forward in establishing collaborations with Nigeria through the University of Jos (UJ), established in 1971 and which began student admission in 1975.